MEMBONGKAR POSITIVISME HUKUM DALAM KUHP PERSPEKTIF HUKUM ISLAM UPAYA MENEGAKKAN KEADILAN HAM KAUM PEREMPUAN DI INDONESIA - Habib Shulton Asnawi (Postgraduate State Islamic Institute (IAIN) Metro, 2013)
Law enforcement (judges, prosecutors and police) in Indonesia is still dominated by the positivistic paradigm and-legalistic way of thinking, especially in the legal meaning of the Criminal Code. The way to think of this kind proved to make the process of law enforcement in Indonesia is arid dry from morality. As a result, justice becomes the ultimate goal of law is often not achieved. Especially is justice and Human Rights (HAM) women. The inequality of women is certainly contrary to the concept of Indonesia as the